APPLICATION OF DEEP LEARNING LEARNING MODEL TO IMPROVE CRITICAL THINKING ABILITIES OF GRADE VIII STUDENTS ON VIBRATION AND WAVE MATERIALS AT SMPN 2 BOJONEGARA, SERANG REGENCY - Nuraeni, Dede Eni; Sajiman, Supardi Uji (Yayasan Education and Social Center, 2025)
This study aims to determine the effectiveness of the application of the deep learning model in improving critical thinking skills of grade VIII students on vibration and wave material at SMPN 2 Bojonegara, Serang Regency. The study used a qualitative method with observation, interviews, and documentation as data collection techniques. The results showed that the application of the deep learning model increased students' active participation and critical thinking skills including analysis, evaluation, and reflection on learning materials. In addition, students also showed a better understanding of the concept of vibration and waves. The obstacles encountered were time constraints and variations in students' initial readiness in participating in learning. This study concludes that the deep learning model can be an effective alternative in improving students' critical thinking skills on physics material at the junior high school level. Recommendations are given to teachers to continue to improve their competence in implementing this model optimally.